Potential for cassava breeding in Asia - Kawano, K (International Center for Tropical Agriculture, 1982)
Feasible overall goals for cassava breeding in Asia are proposed on the basis of current national cassava breeding programs, achievements, and cassava demand in the following Asian Countries: Thailand, Philippines, China, Malaysia, Indonesia, India, and Vietnam. CIAT germplasm that has been selected in Asian countries for outstanding traits is mentioned, among which are CM 305-13, CM 407-7, M Col 1684 hybrids, M Col 1468, and M Bra 12. If the current level of productivity is not significantly increased, the demand for cassava in Asia will not increase; on the other hand, demand will be unrestricted if a major improvement in productivity can be made and cassava can compete with maize, sorghum, and sugarcane. Three levels of research selection goals can be set: in the 1st, research is justified based on the importance of cassava but breeding objectives and goals are not defined, in the 2nd, research goals specify yield, DM content, and resistance to major diseases and pests as primary breeding objectives (30-50 percent yield increase in exptl. stations and 20- 30 percent increase in production fields); and in the 3rd, research goals consider high yield increases to allow cassava to compete favorably with other crops as an energy source (100 percent yield increase, or 50 t/ha, in exptl. stations and 50 percent yield increase, or 25 t/ha, in production fields). (CIAT)